Solid Phase Extraction and Spectrophotometric Method for Determination of Trace Gold with Octyl Benzimidazole Sulfide - Huang, Zhangjie; Zhang, Jun; Chang, Jun; Feng, Shaoping; Yang, Zhongqi (Asian Journal of Chemistry, 2010)
Synthesis and application of octyl benzimidazole sulfide (OBMS), as a new chromogenic reagent for the determination of gold has been described. Highly sensitive, selective and fast method for determination of gold based on its rapid reaction with OBMS and the solid phase extraction of the colored complex on a nonpolar resin MCI GEL CHP 20P has been developed. In the presence of 0.02-0.2 mol L-1 of HCl solution and cetyl trimethylammonium bromide (CTMAB) medium, OBMS reacted with gold to form colored complex of gold-to-OBMS molar ratio of 1:2. The complex was enriched by the solid phase extraction with the MCI GEL CHP 20P cartridge. The complex was eluted from the cartridge with isopentyl alcohol and enrichment factor of 100 was achieved. In isopentyl alcohol medium, molar absorptivity of the complex was 2.77 × 105 L mol-1 cm-1 at 490 nm. Beer's law was obeyed in the concentration range 0.01 ca. 0.8 μg mL-1. The relative standard deviation for 11 replicate samples at the 0.5 μg L-1 level was 2.5 %. In the original sample detection limit was 0.04 μg L-1. This method was applied to the determination of trace gold in ore samples with good result.